Suggested Index for studying violent by Environment and Psychology components among Collegian students at a sample in Baghdad City - ali, Abdulkhaleq; Mecheser, Abdullah (Iraqi National Journal of Nursing Specialties, 2015)
Objective: To identification environmental and psychological violence’s components among collegians’ students of different stages, and gender throughout creating specific questionnaire, and estimating regression of environmental domain effect on psychological domain, as well as measuring powerful of the association contingency between violence’s domains in admixed form with respondent characteristics, such that (Demographics, Economics, and Behaviors), and extracting model of estimates impact of studied domains in studying risks, and protective factors among collegians’ students in Baghdad city. Methodology: Descriptive analysis was processed on collegians’ students during the period from 1-10-2012 to 30- 12- 2012 to assess psychological violence at the collegian environment through studied effectiveness of risk and protective factors. The study was purposive no probability sampling carried out (101) on students, and they are accounted (47) male and (54) female from different stages of study. The study are depended on psychological and environmental violence through different accredited references from previous study with making appropriate amendment, as well as taking of expert’s consideration during the pilot study (Validity), which be in agreement and support. In addition to that, reliability coefficient (Alpha (Cronbach)) for internal consistency shows a highly credit, which indicating that generalization of the study results could be applicable for the population individuals. Descriptive statistics methods are used (Observed frequencies, Percentages, Mean of score, Standard deviation, Relative sufficiency) to assess psychological and environmental violence, as well as inferential statistics methods (Simple linear regression analysis, Contingency association coefficient, and Factor analysis). Results: The results shows that most students are faced to psychological violence upward than environmental violence in the adytum university, with highly relationship between then at (P<0.000), as well as no significant relationships for the contingency associations are accounted between characteristics variables, such that (Demographics, Economic, and some related variables) of studying individuals with their responses assessed through (under/upper) cutoff point (66.67) along psychological and environmental violence items in compact form, and that was achieved by redistribution of global mean of score, and that indicating highly fitness of studying both measurements to assess the population individuals rather than differences concerning with their characteristics variables. Extracted of one factor in factor analysis indicated that participation of both measurements are interacted for appointment responses levels to assess psychological and environmental violence and that formative 79.279% for interpreted the violence level in collegian environment among total sources of violence occur. Recommendation: Introduces some recommendation, and was among the significant of establishing psychological and educational guidance unit at universities for active subscribed of aggravation resources of violence with their different formative and gives a suitable treatments.